Hybrid hematite/calcium ferrite fibers by solution blow spinning: Microstructural, optical and magnetic characterization. Issue 23 (1st December 2021) - Araujo, R.N.; Nascimento, E.P.; Raimundo, R.A.; Macedo, D.A.; Mastelaro, V.R.; Neves, G.A.; Morales, M.A.; Menezes, R.R.
Abstract: Iron oxide and Ca-doped ferrite fibers were successfully prepared via Solution Blow Spinning (SBS). Fibers with several calcium contents (nFe/nCa = 3.0, 5.2, and 20.0 atomic ratio) were prepared after dissolving polyvinylpyrrolidone and Fe and Ca nitrates in an acidic aqueous solution, followed by SBS spinning and calcination at 800 °C. The morphological, structural, optical, vibrational, and magnetic properties of the fibers were evaluated by scanning electron microscopy (SEM), X-ray diffraction (XRD), UV–Vis diffuse reflectance spectroscopy (DRS), Mössbauer spectroscopy, and magnetometry . The Rietveld refinement revealed Ca-doped fibers consisting of a mixture of Fe2 O3, CaFe2 O4, and Ca3.6 Fe14.4 O25.2 crystalline phases. The Mössbauer spectra at 300 K showed a sextet belonging to the hematite phase and two doublets belonging to the calcium-related phases. Measurements at low temperatures showed a transition at 181.6 K attributed to Ca ferrite. The hematite fibers showed a saturation magnetization (Ms 0.75 emu/g) relatively higher than the bulk α-Fe2 O3 (Ms = 0.3 emu/g). The saturation magnetization increased from 3.6 to 6.4 emu/g with increasing Ca content. Highlights: First time hematite/calcium ferrite fibers were produced by solution blow spinning. Small amount of calcium caused structural distortion in hematite and increased its lattice parameters. Small amount of calcium induces a higher saturation magnetization, the non-magnetic character of calcium.